Decolonizing the Psalter in Africa - Adamo, David T. (Black Theology, 2007)
AbstractThis article offers a postcolonial critique of much Western, Eurocentric engagement with the Psalms. The author summarizes the main methodological approaches used by predominantly Eurocentric scholarship in their exegetical work with the Psalms, arguing that these developments have become the dominant models for understanding this literature for all scholars, particularly for biblical scholars from the African continent. This article challenges this existing dominance and provides a brief resume of a number of alternative approaches that have emerged from and are consonant with African cultures and traditions.
paid